Peluang dan Tantangan Transformasi Digital Sertifikat Tanah Setelah Berlakunya Peraturan Menteri ATR/BPN Nomor 3 Tahun 2023 - Ibrahim Rusli Junior (Lembaga Pengembangan Kinerja Dosen, 2026)
The digital transformation of Indonesia's land registration system is marked by the issuance of the Regulation of the Minister of Agrarian Affairs and Spatial Planning/National Land Agency (ATR/BPN) Number 3 of 2023 concerning Electronic Certificates. This study aims to analyze the opportunities, challenges, and regulatory barriers in the transition from conventional to electronic certificates. The research method employed is normative legal research wiqth statutory and case approaches. The results indicate that electronic certificates offer opportunities for administrative efficiency, data transparency, and evidentiary power equivalent to physical certificates. However, implementation faces challenges such as uneven technological infrastructure in rural areas, low digital literacy among the public, and legal misalignment between Permen ATR/BPN Number 3 of 2023 and Government Regulation Number 40 of 1996, which still refers to conventional certificates. In conclusion, regulatory harmonization and equitable distribution of digital infrastructure are required to ensure legal certainty and the success of the national land service transformation.